Semantic web for the working ontologist : effective modeling for linked data, RDFS, and OWL - Allemang, Dean; Hendler, James A.; Gandon, Fabien (ACM books, 2020)
"This book discusses the capabilities of Linked-Data and the Semantic Web modeling languages, such as RDFS (Resource Description Framework Schema) and OWL (Web Ontology Language) as well as more recent standards based on these. The book provides examples to illustrate the use of Semantic Web technologies in solving common modeling problems with many exercises and examples of the use of the techniques. The book provides an overview of the Semantic Web and aspects of the Web and its architecture relevant to Linked Data. It then discusses semantic modeling and how it can support the development from chaotic information gathering to one characterized by information sharing, cooperation, and collaboration. It also explains the use of RDF and linked-data to implement the Semantic Web by allowing information to be distributed over the Web or over intranets, along with the use of SPARQL to access RDF data. Moreover, the reader is introduced to components that make up a Semantic Web deployment and how they fit together, the concept of inferencing in the Semantic Web, and how RDFS differs from other schema languages. In addition, the 2015 "Linked Data Platform" standard is also explored. The book also considers the use of SKOS (Simple Knowledge Organization System) to manage vocabularies by taking advantage of the inferencing structure of RDFS-Plus. It also presents SHACL, a language for checking graph constraints in linked data systems, and a number of useful ontologies including schema.org, the most successfully deployed Semantic Web technology to date. This book is intended for the linked data and semantic Web practitioner looking for clues on how to add more expressivity to allow better linking and use both on the web and in the enterprise, and for the working ontologist who is trying to create a domain model on the Semantic Web."--